Patient reported outcome measures (PROMS) and patient reported experience measures (PREMS): Measuring outcomes in pelvic venous disorders - Sriram Narayanan (Turkish Journal of Vascular Surgery)
Pelvic venous disorders (PeVD) present with a range of heterogenous symptoms that arise from altered venous hemodynamics in the pelvis. Many of these symptoms lead to mental health and quality of life issues and are not limited to the pelvic region. The nutcracker phenomenon causing left renal vein compression and left ovarian venous hypertension as well as the compression of the left common iliac vein by the overlying right common iliac artery are often stated as the common underlying pathologies. As a result, there has been a sudden increase in the number of ovarian vein coil embolizations and iliac vein stents placed. In truth however, the altered venous hemodynamics in PeVD is more complex. There appears to be little correlation between the symptoms patients experience and the obvious image detected anatomical lesions being treated. In addition, these anatomical lesions are very commonly seen in asymptomatic and especially muti-parous women as well. To compare outcomes of these and other more extensive procedures being performed for these commonly seen anatomical changes in the pelvic veins, objective assessments of the outcomes as seen from the symptom relief they bring to patients treated is essential. Validated Patient-reported outcome measures (PROMS) can be an important tool to compare outcomes across interventions for PeVD. However, as the impact of similar symptoms on different patients' quality of life (QoL) can vary, developing a validated PROM that can be used to compare procedural outcomes in PeVD is a challenge. On the other hand, complications and procedural success as reported by physician do not assess the effect on a patient's QoL. This paper provides a narrative review of PROMs, patient reported experience measures (PREMs) and individualized-PROMs. It also suggests a process for how a validated PROM for comparing procedural outcomes in PeVD may be developed. This could provide a framework that incorporates the recently adopted Symptoms-Varices-Pathophysiology (SVP) classification of pelvic venous disorders into the PROM development process to ensure that a like-for-like comparison is made between procedures being performed on a very heterogenous, but long-suffering group of patients. [Turk J Vasc Surg 2023; 32(0.000): 34-8]